'The disease isn't listening to the drug': The socio-cultural context of antibiotic use for viral respiratory infections in rural Uganda. Issue 5 (4th May 2019) - Yantzi, Rachel; van de Walle, Gabriel; Lin, Janet
ABSTRACT: To identify factors precipitating antibiotic misuse and discuss how to promote safe antibiotics use and curb antibiotic resistance. Antibiotic misuse is a significant problem globally, leading to increased antibiotic resistance. Many socio-cultural factors facilitate antibiotic misuse: patient and provider beliefs about antibiotics, inadequate regulation, poor health literacy, inadequate healthcare provider training, and sub-optimal diagnostic capability. This study investigates the influence of such factors on antibiotic use and community health in rural Uganda. Attention was paid to patient-provider dynamics, providers' concerns, and the role of drug shops in the communities and how these situations exacerbate antibiotic misuse. Using a grounded ethnographic approach, interviews, focus groups, and observations were conducted over six weeks. Five salient themes emerged from data analysis. Based on the study results and a review of past literature on antibiotic resistance, there is need for improved health literacy and education, continued focus on efficiency and affordability in healthcare, and recognition of the role of stewardship and government in providing better healthcare. The problem of antibiotic misuse is multifactorial. Proposed solutions must target multiple contributing factors and must ultimately modify the culture and beliefs surrounding antibiotic use and encourage proper use. Such a multi-pronged approach would be most effective and would decrease rates of antibiotic resistance.